FACE-TO-FACE TANDEM AS LANGUAGE LEARNING AND SOCIAL INTEGRATION FOR STUDENTS OF PORTUGUESE AS A FOREIGN LANGUAGE AT CELIN UFPR, BRAZIL - Loires Diniz Trujillo, Gabriela; Pupatto Ruano, Bruna (Revista X, 2017)
Firstly, this article provides an overview of Tandem as a method for learning foreign languages. Secondly, the context in which the project Núcleo Tandem Celin is set is explained thoroughly as we go through the history and structure of Celin (UFPR Intercultural Language Center). Afterwards, the Portuguese as a Foreign Language (PFL) course is put into focus, outlining the growth on the number of foreign students in Curitiba, and the consequences it entails. We also provide an in-depth analysis at the project by explaining its processes and methodology, through current and past experiences. Therefore, we explore the reformulation of the program in which measures to establish its institutional recognition and to attribute the mediation process a pivotal role which ensured its success and sustainability. Finally, we present a testimonial from a student enrolled in the project in order to illustrate the participants’ experience.